Pengaruh Gender, Pertimbangan Pasar Kerja, Lingkungan Kerja Terhadap Pemilihan Karir Profesi Akuntan - Ayu Rakhma Wuryandini; Noval Amrain; Imran Rosman Hambali (Jambura Accounting Review, 2021)
The purpose of this study was to analyze the influence of gender, labor market considerations and work environment on career choice as an accounting profession for accounting students at universities in Gorontalo Province. This type of quantitative research is used in this study with multiple regression as an analytical technique. One university and 3 private universities in Gorontalo Province were used as the population and the sample of this study was accounting students in semester VII of 74 students obtained from simple random sampling. The results of this study indicate that partially gender has a positive but not significant effect on career choice as an accountant profession, labor market considerations have a positive and significant effect on career choice as an accountant profession, and work environment has a positive and significant effect on career choice as an accountant profession. Simultaneously, the variables of Gender, Labor Market Considerations, and Work Environment have a positive and significant effect on career choice as an accountant profession. The variables of gender, labor market considerations, and work environment were able to explain the choice of career as an accounting profession by 36.9% while the remaining 63.1% was influenced by other variables not explained in this study.